Application of a simplified method of chloroplast enrichment to small amounts of tissue for chloroplast genome sequencing1. (8th May 2017) - Sakaguchi, Shota; Ueno, Saneyoshi; Tsumura, Yoshihiko; Setoguchi, Hiroaki; Ito, Motomi; Hattori, Chie; Nozoe, Shogo; Takahashi, Daiki; Nakamasu, Riku; Sakagami, Taishi; Lannuzel, Guillaume; Fogliani, Bruno; et al.
Abstract : Premise of the study: High‐throughput sequencing of genomic DNA can recover complete chloroplast genome sequences, but the sequence data are usually dominated by sequences from nuclear/mitochondrial genomes. To overcome this deficiency, a simple enrichment method for chloroplast DNA from small amounts of plant tissue was tested for eight plant species including a gymnosperm and various angiosperms. Methods: Chloroplasts were enriched using a high‐salt isolation buffer without any step gradient procedures, and enriched chloroplast DNA was sequenced by multiplexed high‐throughput sequencing. Results: Using this simple method, significant enrichment of chloroplast DNA‐derived reads was attained, allowing deep sequencing of chloroplast genomes. As an example, the chloroplast genome of the conifer Callitris sulcata was assembled, from which polymorphic microsatellite loci were isolated successfully. Discussion: This chloroplast enrichment method from small amounts of plant tissue will be particularly useful for studies that use sequencers with relatively small throughput and that cannot use large amounts of tissue (e.g., for endangered species).